Evaluation of Efficiency of Groundwater Desalination Plants in Different Hydrogeological Conditions in Salahaddin Governorate/ Iraq - Manahil A. Mahmood Al-Bayati; Sabbar A. Saleh; Waleed M. Al-Abdraba (Tikrit Journal of Pure Science, 2023)
Five groundwater desalination plants elected in the province of Salahuddin, these plants are Rimth, AlRaml, Albo Hamed, Albo Rahil, and Mcelila which supplied from Al-Naamah, Zgiton, Baiji-Tikrit, West Samarra, and West Makhoul hydrogeological basins respectively.